Radiation therapy for nasopharyngeal carcinoma: the predictive value of interim survival assessment. (30th September 2016) - Toya, Ryo; Murakami, Ryuji; Saito, Tetsuo; Murakami, Daizo; Matsuyama, Tomohiko; Baba, Yuji; Nishimura, Ryuichi; Hirai, Toshinori; Semba, Akiko; Yumoto, Eiji; Yamashita, Yasuyuki; Oya, Natsuo
Abstract: Pretreatment characteristics are suggested as predictive and/or prognostic factors for nasopharyngeal carcinoma (NPC); however, individual tumor radiosensitivities have previously not been considered. As boost planning is recommended for NPC, we performed interim assessments of magnetic resonance (MR) images for boost planning and retrospectively evaluated their predictive value for the survival of NPC patients. Radiation therapy via elective nodal irradiation (median dose: 39.6 Gy) with/without chemotherapy was used to treat 63 NPC patients. Boost irradiation (median total dose: 70 Gy) was performed based on the interim assessment. The largest lymph node (LN) was measured on MR images acquired at the time of interim assessment. The site of first failure was local in 8 (12.7%), regional in 7 (11.1%), and distant in 12 patients (19.0%). All 7 patients with regional failure harbored LNs ≥15 mm at interim assessment. We divided the 63 patients into two groups based on LN size [large (≥15 mm), n  = 10 and small (<15 mm), n  = 53]. Univariate analysis showed that 5-year overall survival (OS) and cause-specific survival (CSS) rates for large LNs were significantly lower than for small LNs (OS: 12.5% vs 70.5%, P  < 0.001 and CSS: 25.0% vs 80.0%, P  < 0.001). Multivariate analysis showed that large LNs were a significantly unfavorable factor for both OS (hazard ratio = 4.543, P  = 0.002) and CSS (hazard ratio = 6.020, P  = 0.001). The results suggest that LN size at interim assessment could predict survival in NPC patients.